Integrated Nutrient Management on the Yield and Profitability of Cauliflower (Bangladesh Agronomy Journal, 2021)
Field experiments were conducted at Multi Location Testing (MLT) sites of Chandina and Debidwer of Cumilla district, and Kasba of Brahmanbaria district under on-farm research division (OFRD), Bangladesh Agricultural Research Institute, Cumilla during 2016-18 to find out the appropriate dose of fertilizer for the maximum productivity of hybrid cauliflower varieties. Five integrated nutrient management packages  such as T1= Recommended fertilizer dose for high yield goal (HYG), viz. 40-20-38-7-0-0 NPKSZnB Kg ha-1, T2= T1 + 1.5 t ha-1 vermicompost, T3 = T1 + 5 t ha-1 cowdung, T4= STB  (107-61-107-30-3.0-1.0 NPKSZnB Kg ha-1 and T5= Farmers practices  (114-74-123.5-0-0 NPKSZnB Kg ha-1) were used in the trial. The experiment was laid out in a Randomized Complete Block (RCB) design with six dispersed replications. The result revealed that the highest curd breadth (21.68 cm), individual curd weight (1.86 Kg) and curd yield (44.14 t ha-1) was obtained from T2 treatment followed by T3 and T4 treatments. The lowest yield was found from farmers practice. Similarly the highest gross return (Tk. 626669.00 ha-1) and gross margin (Tk. 493869.00 ha-1) were also found from T2 treatment and the lowest (Tk. 457734.00 ha-1 and 438066.00 ha-1) respectively from  farmer's practice T5.Bangladesh Agron. J. 2020, 23(2): 45-49